A wedding for julia ebook - Chapman, Vannetta (Pebble Creek Amish, 2013)
A Wedding for Julia , the third book in a romantic series from popular author Vannetta Chapman, takes a last look at the Amish community of Pebble Creek and the kind, caring people there. As they face challenges from the English world, they come together to reach out to their non-Amish neighbors while still preserving their cherished Plain ways. Julia Beechy is so stunned, she can hardly breathe. Her mother's announcement that she must either marry or move from the family home upon her mother's imminent death catches Julia by surprise. How can she leave the only home she has ever known? What about her dream of opening her own Plain café? When Caleb Zook offers support, comfort, and a solution, Julia is afraid to accept it. Can she marry someone she barely knows? Is it the right thing to do? Is this God's plan for her future? Caleb thought his time for marrying was long past, but he feels a stirring in his heart he cannot shake for this beautiful, forlorn woman. Amid the circumstances of this life-altering decision, the people of Pebble Creek weather the worst storm to hit Wisconsin in the last hundred years. Where will Julia and Caleb be on the other side of it?